Analisis Persaingan Ojek Online Pada Aplikasi Gojek, Maxim Dan Grab - Wananda Purna Maulidi; Hani Fatu Zahra; Syamsul Hidayat (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
Competition comes from English, namely competition means competition itself or competitive activities, matches, and competition. Competition is when organizations or individuals compete to achieve desired goals such as consumers, share market, survey ranking, or required resources. Whereas In the management dictionary, competition is the efforts of 2 parties/more companies, each of which is active in “obtaining order” by offering the most favorable price/terms. In the online motorcycle taxi industry, competition between companies such as Gojek, Maxim and Grab is very tight. Each company tries to attract more drivers and users by offering various promotions, discounts and additional services. They also compete in terms of technological innovation, such as developing new features to make it easier for users to order motorbike taxis, as well as increasing efficiency in their systems. Apart from that, price competition is also a major factor, where every company tries to offer competitive rates to attract more customers. The method used in this research is a quantitative or statistical method. The population in this research is all odd semester Management students at Bina Bangsa University, namely 73 respondents. Based on the results of research on 73 respondents and discussion regarding online motorcycle taxi competition on the Gojek, Maxim and applications. Seize. It can be concluded that the respondents who use online motorcycle taxis at odd semester Management students at Bina Bangsa University frequently use online transportation, namely the Maxim application because it is cheaper than the Gojek and Grab applications.